2010
DOI: 10.1111/j.1751-553x.2010.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the neutrophil myeloperoxidase index and subsets of bacterial infections

Abstract: The mean myeloperoxidase index (MPXI) is calculated during the routine complete blood count performed using the autoanalyzer ADVIA120/2120. The pattern of changes in the neutrophil myeloperoxidase levels in patients with specific infectious diseases was analyzed by assessing the MPXI levels. In patients with bacterial sepsis, identified by positive blood-culture tests, with (n = 29) and without (n = 51) systemic inflammatory response syndrome, the mean MPXI significantly reduced to -3.18 and -2.06, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 8 publications
(10 reference statements)
4
27
0
Order By: Relevance
“…Yonezawa et al [26] found that elevated MPXI indicates increased MPO activities microbicidal activities in an infectious state. However, in severe bacterial infections such as sepsis, the activated neutrophils release large amounts of MPO for bactericidal activities, and an increase in degranulated neutrophils can reduce the MPXI values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yonezawa et al [26] found that elevated MPXI indicates increased MPO activities microbicidal activities in an infectious state. However, in severe bacterial infections such as sepsis, the activated neutrophils release large amounts of MPO for bactericidal activities, and an increase in degranulated neutrophils can reduce the MPXI values.…”
Section: Discussionmentioning
confidence: 99%
“…As stained WBC pass through the flow cell, light scatter (y-axis) and absorbance (x-axis) are measured by a tungsten-halogen light source, and the MPXI is defined by the deviation from the mean neutrophil values on the x-axis. [26] Several biomarkers, such as serum CRP, require additional laboratory processes and expenses, whereas serum DNI and MPXI analyses do not. This is due to the fact that they are routinely performed with leukocyte differential counts in clinical settings, enabling the results to be obtained simultaneously with WBC counts and neutrophil fractions in complete blood count (CBC) testing.…”
Section: Methodsmentioning
confidence: 99%
“…These changes may be identified by a calculated myeloperoxidase index (MPXI) reflecting staining intensity, and by changes in location of neutrophils in the Perox dot plot. Decreased MPXI in neutrophils was reported to be of diagnostic value in evaluation of horses with systemic inflammation and people with sepsis . In contrast, MPXI was increased in a study of foals with neutropenia and sepsis .…”
Section: Introductionmentioning
confidence: 93%
“…DNI has been known to be significantly associated with disseminated intravascular coagulation scores, positive blood culture rate and mortality in patients who are suspected to have sepsis 19. Park et al reported that DNI may be used as a marker of disease severity in critically ill patients with sepsis 12. Although this study was ED based while Park et al 's study was intensive care unit based, we also showed higher DNI in sepsis versus non-infectious SIRS groups (table 2).…”
Section: Discussionmentioning
confidence: 43%
“…Second, infection was not defined by microbiological tests in all patients. Third, MPO activity may be unchanged in certain infectious diseases as is the case with tuberculosis, in which the immune response involves mainly T lymphocytes and macrophages, and in viral diseases 12. Further investigation is warranted on the significance of MPXI, alone or in addition with other inflammatory markers, for diagnostic and prognostic differentiation in SIRS.…”
Section: Discussionmentioning
confidence: 99%